Pancasila Student Profile Policy to Create a Superior Generation in Facing the Era of Society 5.0 and Its Implications for Personal Resilience - Ravyansah; Nur Ekowati, Puji; Ardiansyah, Hendro (Internasional Journal of Politics and Public Policy, 2025)
Modern life dynamics require educational policies that are responsive to contemporary needs. One such policy is the Profile Pancasila Students (Pancasila Student Profile), which embodies Pancasila values to shape students as globally minded individuals while maintaining Indonesian identity. This study examines the policy as an effort to build an excellent young generation in the era of Society 5.0, emphasizing personal resilience as the foundation of national resilience. Using a qualitative descriptive method with literature study, the research reveals that Society 5.0 presents both challenges and opportunities. Global integration can broaden perspectives, enhance creativity, and strengthen competitiveness, contributing positively to national progress. However, it also carries the risk of weakening cultural identity if not addressed wisely. In this context, the Pancasila Student Profile plays a crucial role in preparing students who are resilient, globally competent, and grounded in Pancasila values. Ultimately, this policy contributes to fostering personal resilience that serves as a pillar of Indonesia's national resilience.